Covid-19: Organizações questionam gastos do Governo moçambicano | DW | 11.08.2020 - Deutsche Welle (DW.COM, 2020)
Em Moçambique, a sociedade civil aponta falta de transparência e pede esclarecimentos ao Governo sobre os 14 mil contratos sem concurso público e os 68 mil milhões de meticais gastos durante o estado de emergência.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; health - COVID-19 / saúde – COVID-19; health / saúde; transparency / transparência

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência

Relatório De Diagnóstico Sobre Transparência, Governação E Corrupção - República de Moçambique (International Monetary Fund (IMF), 2019)
A economia de Moçambique encontra-se num ponto de viragem, e os esforços para abordar as vulnerabilidades em matéria de governação e corrupção podem ter um impacto positivo duradouro. Já tomámos medidas para abordar as vulnerabilidades em matéria de governação e corrupção. Contudo, reconhecemos que subsistem falhas em diversas áreas relevantes da economia. A fim de abordar algumas das debilidades restantes, temos reformas de governação em curso e em perspectiva em várias áreas, muitas delas apoiadas por diversos doadores. Reconhecemos que a implementação eficaz continua a suscitar preocupações. Reconhecemos que a falta de transparência pode igualmente exacerbar as preocupações com a governação e agravar o risco de conflitos de interesse. Embora reconheçamos que temos um papel essencial a cumprir na melhoria da governação e no combate à corrupção, não podemos fazê-lo sozinhos. Estamos preparados e dispostos a tomar medidas concretas.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; corruption / corrupção; transparency / transparência

Social Accountability: What Does the Evidence Really Say? - Fox, Jonathan A. (World Development, 2015)
Empirical evidence of tangible impacts of social accountability initiatives is mixed. This meta-analysis reinterprets evaluations through a new lens: the distinction between tactical and strategic approaches to the promotion of citizen voice to contribute to improved public sector performance. Field experiments study bounded, tactical interventions based on optimistic assumptions about the power of information alone, both to motivate collective action and to influence the state. Enabling environments for collective action combined with bolstered state capacity to respond to citizen voice are more promising. Sandwich strategies can help ‘voice’ and ‘teeth’ to become mutually empowering, through state–society synergy.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; transparency / transparência

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência